How are the kids? Psychosocial wellbeing and needs of the offspring of breast cancer patients - Chih, Hui Jun; Chan, Arlene; Lomma, Chris; Reid, Christopher (2019)
Background: Cancer diagnosis impacts not only on the patients but their family. Impact of patients’ cancer stage on psychosocial distress or needs in their offspring has not been extensively studied. Aim: To assess incidence of psychosocial distress and needs experienced in 14-24 year-old offspring of women with early or metastatic breast cancer. Methods: Cross-sectional survey of 120 offspring of early and metastatic female breast cancer patients was conducted in Perth, Western Australia. Kessler Psychological Distress Scale (K-10) and Offspring Cancer Needs Instrument (OCNI-47) were used. Difference in distress score by sex of offspring were assessed using independent samples t-test. Prevalence of distress (low/moderate/high/very high) and needs were reported by maternal cancer stage and their associations assessed using Chi-squared tests. Results: Female offspring reported significantly higher distress (p=0.017) than male offspring. Percentages of low, moderate, high and very high levels of distress among offspring of early stage breast cancer mothers were 31.5%, 38%, 21% and 9.5%, respectively. More offspring of metastatic patients reported moderate distress (44%) and very high distress (12%). Stage of cancer was associated with needs (p<0.05). Unmet needs of the offspring of early stage cancer was in the domain of “information about parent’s cancer” while unmet need among offspring of metastatic patients was “dealing with feelings”. Needs in the domain of “dealing with feelings” were reported as being met by offspring of early stage cancer patients. Conclusions: Female offspring and offspring of metastatic patients were more distressed. Areas of met and unmet psychosocial needs of offspring differ by cancer stage of their mothers. ‘So what’/Implications: This present study identified a different impact on psychosocial wellbeing and needs of offspring. The findings can inform the development of support programs for young people with mothers diagnosed with breast cancer, based on their sex, and stage of their mother’s cancer stage.